Drea, Macarthur’s Ultra - Codebreaking and The War Against Japan, 1942-1945 - Pennington, Loren (Teaching History: A Journal of Methods, 1994)
World War II intelligence operations in the Pacific have been of intense interest to historians since the 1940s and the debate over the Pearl Harbor debacle. But in the 1970s, and especially after the publication of F. W. Winterbottom’s bestseller The Ultra Secret, interest in intelligence has focused increasingly on the European theater. The time now seems appropriate for a fresh look at intelligence in the Pacific, and Edward J. Drea’s MacArthur’s Ultra, though limited to the Southwest Pacific, is an excellent beginning.